Asksia AI LOGO

Sia

Question
Math
Posted 10 months ago
f(x)=6f(x)f^{\prime}(x)=-6 f(x), and f(2)=1f(2)=1.
Solve the equation.

Choose 1 answer:
(A) f(x)=12e6xf(x)=-12 e^{-6 x}
(B) f(x)=e6xf(x)=e^{-6 x}
(C) f(x)=e126xf(x)=e^{12-6 x}
(D) f(x)=2exf(x)=2 e^{-x}
Sign in to unlock the answer
Answer from Sia
Posted 10 months ago
Solution by Steps
step 1
Solve the differential equation f(x)=6f(x)f'(x) = -6f(x) using separation of variables
step 2
The general solution is f(x)=c1e6xf(x) = c_1 e^{-6x}, where c1c_1 is a constant
step 3
Apply the initial condition f(2)=1f(2) = 1 to find the value of c1c_1
step 4
Substitute x=2x = 2 into the general solution to get 1=c1e121 = c_1 e^{-12}
step 5
Solve for c1c_1 to get c1=e12c_1 = e^{12}
step 6
Substitute c1c_1 back into the general solution to get the specific solution f(x)=e126xf(x) = e^{12-6x}
Answer
f(x)=e126xf(x) = e^{12-6x}
Key Concept
Solving first-order linear ordinary differential equations with initial conditions
Explanation
The solution to the differential equation is found by integrating both sides and then applying the given initial condition to solve for the constant of integration.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question